2014
DOI: 10.1051/bioconf/20140302007
|View full text |Cite
|
Sign up to set email alerts
|

Reducing pesticide level in wine by selective filtration

Abstract: Abstract. Wine Pesticide residues, even when below grape regulatory limit, are a concern for consumers and have an impact on the export potential of wine in certain markets. A consortium of European SMEs (www.adfimax.com) has developed a product that reduces the level of mycotoxins and pesticides in wine while keeping all other wine parameter identical. The product is derived from renewable vegetable fiber. The production process includes both activation and micronisation. The usage recommendation is to substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As it has been suggested that selective vegetal fibres might absorb phenolic compounds [4], the red wines filtered with the laboratory pilot device were analyzed chemically ( Table 5). The measured values show indeed a slight reduction of color intensity, total polyphenolic index, and anthocyanins especially for the highest amount of selective fibres.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it has been suggested that selective vegetal fibres might absorb phenolic compounds [4], the red wines filtered with the laboratory pilot device were analyzed chemically ( Table 5). The measured values show indeed a slight reduction of color intensity, total polyphenolic index, and anthocyanins especially for the highest amount of selective fibres.…”
Section: Resultsmentioning
confidence: 99%
“…This technology, implemented in wine during filtration, is very effective for certain substances and impacts only little the wine quality [4]. The functional principle is based on a physical phenomenon of adsorption of contaminants present in wine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology developed by the consortium of European SMEs is based on a activated vegetal fibre (AVF) that adsorbs pesticides and other unwanted contaminants such as mycotoxins while not impacting the other characteristics of wine such as color and taste. This activated vegetal fibre (AVF) can be integrated into a filter sheet [1] or directly used as a filter adjuvant [2].…”
Section: Introductionmentioning
confidence: 99%